1997
DOI: 10.1038/sj.gt.3300373
|View full text |Cite
|
Sign up to set email alerts
|

Optimized conditions for the production of recombinant amphotropic retroviral vector preparations

Abstract: The production and stability of recombinant retroviral vecwas reached between retroviral vector production and tors was examined at various temperatures. The two studdecay. Maximal accumulated recombinant retroviral titers ied recombinant retroviral vectors, based on different packwere five-to ten-fold increased after a medium incubation aging cell lines, exhibited a four-fold increased half-life at at 32°C as compared to 37°C. Furthermore, multiple cycles 32°C as compared to 37°C. Surprisingly, this increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 5 publications
8
36
1
Order By: Relevance
“…Although the specific reasons for this thermal sensitivity are not identified, amino acid changes in viral polymerases have produced PIV3 viruses that exhibit temperature-sensitive phenotypes (Feller et al 2000;Skiadopoulos et al 1999). Other virus systems have demonstrated similar thermal sensitivity: the cultivation of retrovirus packaging cells at 32°C instead of 37°C increased the yield of infectious virus particles by a maximum of 2-to 15-fold (Kaptein et al 1997;Kotani et al 1994;Lee et al 1996).…”
Section: Effects Of Time Of Infection and Post-infection Temperature mentioning
confidence: 97%
“…Although the specific reasons for this thermal sensitivity are not identified, amino acid changes in viral polymerases have produced PIV3 viruses that exhibit temperature-sensitive phenotypes (Feller et al 2000;Skiadopoulos et al 1999). Other virus systems have demonstrated similar thermal sensitivity: the cultivation of retrovirus packaging cells at 32°C instead of 37°C increased the yield of infectious virus particles by a maximum of 2-to 15-fold (Kaptein et al 1997;Kotani et al 1994;Lee et al 1996).…”
Section: Effects Of Time Of Infection and Post-infection Temperature mentioning
confidence: 97%
“…Non-viable particles may come from several areas: (1) Viable retrovirus, which has a half-life of 4-8 h at 37°C 21,22 remains in the ECS, becoming thermally inactivated over time and resulting in an increase of non-viable particles in the culture environment. (2) The action of ultrafiltration through the hollow fibre pores results in shearing of the viral envelope, generating viral particles incapable of infection.…”
Section: ᭹ Transduction With Vcm Collected At 32°c; ̅ Transduction mentioning
confidence: 99%
“…Pizzato et al 12 and our earlier studies reported a half-life of the amphotropic MLV pseudotype produced in CEM and PA317 packaging cells, respectively, of approximately 4 h, whereas the same pseudotype produced in FLYA13 and CCRIP packaging cells showed a slightly higher stability. 17,15 GALV and MLV-10A1 pseudotypes produced in the NIH3T3-derived packaging cell lines PG13 and PT67 have half-lives of 13 h and 14 h, respectively. 15 TCR-retrovirus produced in Db-Jurkat/GP+GALV packaging cells efficiently transduced human T-cell lines, whereas the transduction of primary human T cells was lower.…”
Section: Discussionmentioning
confidence: 99%